2003
DOI: 10.2298/avb0303087d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of benzene on serum hormones and the activity of some enzymes in different tissues of rats

Abstract: The effects of a 100 mg.kg -1 dose of benzene, an occupational and environmental toxicant, were investigated on serum, estradiol and testosterone concentrations as well as lactate dehydrogenase (LDH), alkaline phosphatase (ALP), alanine amino transferase (ALT), aspartate amino transferase (AST), and pyruvate kinase (PK) activities in the liver and kidney of rats after 2, 4, 8, 16, 32, 64 and 72 hours. Benzene was given intraperitoneally to Rat rattus norvegicus and the control groups were injected with physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In other study, Kang et al (2007) were found that exposure to polycyclic aromatic hydrocarbons such as benzo(a)pyrene, phenanthrene and pyrene in rats results increase in ALT, AST and ALP activities. Also, Dere et al (2003) were shown that a significant increase in ALT in the liver and in LDH, AST, and ALT in the kidney occurs after exposure to benzene. The increase in the activity of these enzymes in the serum may result only consequent to impairment of the function of tissues with subsequent liberation of the enzymes into the circulation from the damaged tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In other study, Kang et al (2007) were found that exposure to polycyclic aromatic hydrocarbons such as benzo(a)pyrene, phenanthrene and pyrene in rats results increase in ALT, AST and ALP activities. Also, Dere et al (2003) were shown that a significant increase in ALT in the liver and in LDH, AST, and ALT in the kidney occurs after exposure to benzene. The increase in the activity of these enzymes in the serum may result only consequent to impairment of the function of tissues with subsequent liberation of the enzymes into the circulation from the damaged tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Significant increase in the serum albumin and total protein levels in rats treated with SB for 10 days (30). While (31) reported no significant changes in total protein while significant increase serum urea. The benzene formation from reaction of combination SB with Vit.C which inhibits the protein synthesis by inactivating some proteins and damaging DNA and RNA molecules (32).…”
Section: Resultsmentioning
confidence: 81%
“…It is clear that the damage by the effects of benzene will probebly affect all systems. In a study by Egemen et al (2003), it was shown that estradiol and testosterone activities in the serum, lactate dehydrogenase, alkaline phosphatase, alanine amino transferase, aspartate amino transferase, and pyruvate kinase activities in the liver and kidney of rats given a 100 mg.kg -1 dose of benzene were affected. Consequently, they found that benzene caused some changes (increases then decreases) in enzymes and hormone activities in different tissues of rats.…”
Section: Discussionmentioning
confidence: 99%